Urban ethnic encounters : the spatial consequences - Erdentuğ, Aygen, 1949-; Colombijn, Freek, 1961- (Routledge research in population and migration ;, 2003)
This book addresses how urban space structures the life of ethnic groups and how ethnic diversity helps to shape urban space. Material is presented from diverse locations such as the cities of Toronto, Vienna, Beirut, Jakarta and Albuquerque.